Prevalence and risk factors for oral DNA tumor viruses in HIV-infected youth - Kahn, Jessica A. (J Med Virol, 2016)
Human papillomavirus (HPV), Epstein-Barr virus (EBV), and Kaposi sarcoma-associated herpes virus (KSHV) may promote oral cancers, especially among immunosuppressed individuals. The aims of this study were to examine whether demographic characteristics, medical history, sexual behaviors, substance use, CD4+ T-cell count, HIV viral load, and HPV vaccination were associated with HPV, EBV and KSHV infection and viral load. Multivariable modeling using logistic or linear regression examined associations between independent variables and infection or viral load, respectively. Among 272 HIV-infected 12–24 year-old youth, 19.5% were positive for oral HPV, 88.2% for EBV, and 11.8% for KSHV. In multivariable models, recent marijuana use (OR 1.97, 95% CI 1.02–3.82) and lower CD4+ T-cell count (< 350 vs. ≥ 350 cells/mm(3): OR 1.92, 95% CI 1.003–3.69) were associated with HPV infection; lifetime tobacco use (estimated coefficient [EC] 1.55, standard error [SE] 0.53, p=.0052) with HPV viral load; recent tobacco use (OR 2.90, 95% CI 1.06–7.97) and higher HIV viral load (≥ 400 vs. < 400 copies/mL: OR 3.98, 95% CI 1.84–8.74) with EBV infection; Black vs. White race (EC 1.18, SE 0.37, p=.0023) and lower CD4+ T-cell count (EC 0.70, SE 0.28, p=.017) with EBV viral load, male vs. female gender (OR 10, 95% CI 1.32–100) with KSHV infection, and younger age at HIV diagnosis (1–14 vs. 18–20 years: EC 0.33, SE 0.16, p=.049; 15–17 vs. 18–20 years: EC 0.35, SE 0.13, p=.0099) with KSHV viral load. In conclusion, substance use and immunosuppression are associated with oral DNA tumor viruses in HIV-infected youth.